2005
DOI: 10.1152/physiolgenomics.00256.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a QTL region with large effects on growth and fatness on mouse chromosome 2

Abstract: We combined the use of a congenic line and recombinant progeny testing (RPT) to characterize and fine map a previously identified region of distal mouse chromosome 2 (MMU2) harboring quantitative trait loci (QTL) with large effects on growth and fatness. The congenic line [M16i.B6-( D2Mit306- D2Mit52); MB2] was created using an inbred line (M16i) derived from a line that had undergone long-term selection for rapid weight gain (M16) as the recipient for an ∼38-cM region on MMU2 from the inbred line C57BL/6J. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Although this result would be anticipated, it is not clear whether the duplicated gene, which is truncated, is actually functional (37). Given the collective antimicrobial functions of genes within this cluster, an alternative explanation is that cumulative allelic variation in several candidate genes in this region accounts for the overall QTL effect, as has been previously observed for several QTL that were dissected into subregions through congenic analysis (38,39). The mapping power of our approach will increase as we continue into later generations of the AIL (now at G 10 ).…”
Section: Discussionmentioning
confidence: 82%
“…Although this result would be anticipated, it is not clear whether the duplicated gene, which is truncated, is actually functional (37). Given the collective antimicrobial functions of genes within this cluster, an alternative explanation is that cumulative allelic variation in several candidate genes in this region accounts for the overall QTL effect, as has been previously observed for several QTL that were dissected into subregions through congenic analysis (38,39). The mapping power of our approach will increase as we continue into later generations of the AIL (now at G 10 ).…”
Section: Discussionmentioning
confidence: 82%
“…The other region in which we searched for candidate genes was on mouse Chr 2, near D2Mit285, which maps between the midpoint of the chromosome and its telomere. Many studies have identified this distal region of Chr 2 as important in body composition phenotypes, and it is the focus of several positional cloning efforts (Chiu et al 2007;Diament et al 2004;Farber et al 2006;Jerez-Timaure et al 2005). According to our candidate gene analysis, the three genes most likely to underlie the QTL on Chr 2 were adenosine deaminase, cystatin C, and lipopolysaccharide binding protein.…”
Section: Candidate Genesmentioning
confidence: 84%
“…Prior work in our laboratory has validated the DEXA method using a wide range of mouse strains (including B6 and PWK) and suggests that differences between this measure and other measures of body composition are minor. Previous investigators have used this method successfully to conduct genetic analyses of body composition in mice (Jerez-Timaure et al 2005;Masinde et al 2002c;Srivastava et al 2006;Vitarius et al 2006). …”
Section: Body Composition Measurementsmentioning
confidence: 99%
“…DUSP15 displays phosphatase activity against the artificial substrate pNPP in vitro [130], but physiological substrates for DUSP15 have yet to be reported. DUSP15 contains an N-terminal myristoylation signal, resulting in targeting of the protein to plasma membrane [90] and in mice DUSP15 has been identified as a candidate gene in a quantitative trait locus (QTL) thought to harbor genes that control for the predisposition to growth and fatness in mice [131].…”
Section: Dusp15mentioning
confidence: 99%